SISTEM INFORMASI KONTROL STOK BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING (STUDI KASUS: PT. GAJAH TUNGGAL TBK) - Erik Fathur Rohman; Jaka Sutresna (CV. Multi Kreasi Media, 2022)
Currently, the process of recording sticker management in Pt. Gajah Tunggal Tbk is still done in a conventional way that is by writing data into the monthly sticker stock bookkeeping form. There are often problems such as loss of stickers, shortages and delays in sticker stock that cause delays in the delivery of goods to consumers. This research aims to build and design the Sticker Control Stock Information System on PT. Gajah Tunggal Tbk. Benefits of This Research can help and facilitate the performance of Plant Apw warehouse admin in the process of processing sticker stock data. The results of this study are web-based applications. By using a web-based information system is expected to avoid previously frequent errors such as sticker loss, delays and power of sticker stock in Warehouse Apw because it still uses conventional means. The research methods used in system development apply extreme programming and design methods using uml modeling language.